Two new Pristimantis (Anura: Terrarana: Strabomantidae) from the Sierra de Perijá, Venezuela - Barrio-Amorós, César L.; Rojas-Runjaic, Fernando; Barros, Tito R. (Zootaxa, 2010)
Two new species of Pristimantis are described from Cerro Las Antenas, on the Venezuelan versant of the Sierra de Perijá, a region that is being rapidly destroyed by extensive cultivation and civil unrest. The first species (P. lassoalcalai sp. nov.) has dirty-white spots surrounded by black in the groin and on the hidden surfaces of the hind limbs—a characteristic shared by members of the "lentiginosus" group (Rivero 1982) from the Cordillera de Mérida—and marbled to reticulated venter. The second species (P. rivasi sp. nov.) is currently the largest member of the genus known from Perijá, and presents conspicuous cranial crests. The two new species are assigned to the P. unistrigatus species group.